1996
DOI: 10.1002/(sici)1097-4547(19960201)43:3<335::aid-jnr8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA species encoding heat shock protein 90 (hsp90) in control and hyperthermic rabbit brain

Abstract: Northern blot and in situ hybridization were employed to investigate regional and cell type differences in the expression of hsp90 mRNA species in control and hyperthermic rabbit brain. Riboprobes specific to hsp90 α and β mRNA species were utilized in time‐course Northern blot studies on cerebral hemispheres and the cerebellum. Following hyperthermia, levels of hsp90 α and β mRNA were elevated in both brain regions; however, the magnitude of induction was more robust in the cerebellum than in cerebral hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This protein is a useful marker of cellular stress due to their high constitutive levels of hsc70 protein in many cell types; however, previous studies both in [18,20]. In addition to hsc70, neurons express high vivo and in vitro have indicated that induction of hsp70 constitutive levels of hsp90 mRNA and protein which is dampened in several neuronal cell populations folmay also contribute to this buffering [39,40]. Cells lowing heat shock compared to glial cells [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a useful marker of cellular stress due to their high constitutive levels of hsc70 protein in many cell types; however, previous studies both in [18,20]. In addition to hsc70, neurons express high vivo and in vitro have indicated that induction of hsp70 constitutive levels of hsp90 mRNA and protein which is dampened in several neuronal cell populations folmay also contribute to this buffering [39,40]. Cells lowing heat shock compared to glial cells [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…In central nervous system, Hsp90 is widely expressed in all regions at the latest stages of gestation and postnatal development. In the adult mammalian nervous system and at all stages of postnatal development, the Hsp90 constitutively expressed is preferentially localized on neurons [12,13,[17][18][19]. Most studies regarding the role of Hsp90 in nervous system have focused on its involvement on neurodegenerative diseases [20], however its importance in neuron differentiation remains mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of the heat shock proteins (HSPs) are affected by both anaesthetics and, given that HSP70, HSP84b and HSP 90 are known to have neuroprotective roles (7,23,25,26,35,36), this could pose significant risks to neurons during and after anaesthesia. Modulation of proteins like syntaxin B2 and dihydropyrimidinaselike proteins, which are involved in synaptic structure and function (1,2,18,21,22,39), could also have long-term effects on brain circuitry, so it is vital that we understand the outcomes of using particular anaesthetic agents.…”
Section: Discussionmentioning
confidence: 86%